A general method for ultrathin 1D oxide nanomaterials. Issue 35 (12th July 2017) - Zhao, Yuxin; Sun, Bing; Zhang, Shucai; Wang, Lin; Gao, Xin; Liu, Quanzhen; Mu, Shanjun; Zhang, Miao; Hu, Shi; Huo, Ziyang
Abstract : A series of oxide ultrathin nanomaterials are prepared via a general method and the catalytic property is demonstrated in CeO2 . Abstract : By utilizing the interaction between inorganic species and organic surfactants, the ordered layered mesostructures were generated for the synthesis of the one-dimensional oxide nanomaterials. The oxide nanomaterial products which evolved from the above layered structures were demonstrated as ultrathin (less than 2 nm) one-dimensional structures with superior catalytic performance. The synthetic method based on layered structures can be extended to prepare other one-dimensional oxide nanomaterials with the same ultrathin structures.